Identifying the hidden burden of allergic rhinitis (AR) in community pharmacy: a global phenomenon - Tan, Rachel (Asthma Res Pract, 2017)
BACKGROUND: Patients with allergic rhinitis often trivialise their condition, self-manage inappropriately, and would benefit from health care intervention. The primary point of health care contact for these self-managing allergic rhinitis patients is the community pharmacy. With the majority of allergic rhinitis treatments being available for purchase over the counter, without health care professional contact, we know little about how the patients self-manage. This study aims to identify the burden of allergic rhinitis in the community pharmacy and to identify key opportunity for intervention. METHODS: Pharmacy customers, who purchased nasal treatment in a community pharmacy, were approached with a research-administered questionnaire that collected data on medical history, symptoms and products purchased for the treatment of nasal symptoms. RESULTS: Of the 296 participants, 69.9% self-managed with over-the-counter medications; with 68% experiencing allergic rhinitis symptoms and only 44.3% of this subgroup had a doctor’s diagnosis. Nasal congestion (73.6%) was most commonly experienced and oral antihistamines were most commonly purchased (44.3%), indicating a pattern of suboptimal management. A third of participants (36.5%) experienced moderate-severe symptoms, persistently, which impacted on their daily living. Medication selection was mainly based on pharmacy customers’ perceptions of medication effectiveness (47.6%). CONCLUSION: A majority of participants that self-selected over-the-counter medications have symptoms consistent with allergic rhinitis, with almost half not having received a diagnosis. Medication purchasing patterns suggest that sub-optimal therapeutic decisions made by participants, even when they are experiencing significant symptoms. This study uncovers the hidden burden of allergic rhinitis in the community pharmacy and a missed opportunity to intervene and refer if necessary. Patients need to be guided through appropriate treatment as this study showed that many should be referred to a medical practitioner. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40733-017-0036-z) contains supplementary material, which is available to authorized users.